Circumsporozoite protein of Plasmodium berghei: gene cloning and identification of the immunodominant epitopes. - Eichinger, D J (1986)
The gene encoding the circumsporozoite (CS) protein of the rodent malaria parasite Plasmodium berghei was cloned and characterized. A cDNA library made from P. berghei sporozoite RNA was screened with a monoclonal antibody for expression of CS protein epitopes. The resulting cDNA clone was used to isolate the CS protein gene from a lambda library containing parasite blood-stage DNA. The CS protein gene contains a central region encoding two types of tandemly repeated amino acid units, flanked by nonrepeated regions encoding amino- and carboxy-terminal signal and anchorlike sequences, respectively. One of the central repeated amino acid unit types contains the immunodominant epitopes.